Dysentery by CTX-M Type ESBL Producing Shigella flexneri - Garrido, David Israel; Fuseau Herrera, Michelle; Garrido, Santiago Moises; Gutierrez, Miguel; Calvopiña, Leonel; Vivas, Gina (Revista Cubana de Medicina Tropical, 2018)
According to the World Health Organization, diarrheal infections cause 525 000 deaths of children under five years of age every year. Shigellosis is a relevant cause of dysentery which increases morbidity and mortality in pediatric patients. Therefore, the emergence of antimicrobial resistant strains of Shigella is a worrisome problem worldwide. We report the case of a 7-year-old patient with acute dysentery caused by CTX-M Type ESBL Producing Shigella flexneri. This was the first case in the Specialties Hospital of Specialties of the Armed Forces N°1, in Quito, Ecuador. The antibiogram showed sensitivity to ampicillin-sulbactam. As a result, after five days of microbiologically directed treatment, the patient improved his condition without relapse. Proper clinical diagnoses and accurate laboratory studies like stool culture and antibiogram are crucial to indicate an appropriate therapy in infections caused by Shigella and other enteric bacilli.